PEMBELAJARAN BARZANJI MELALUI MODEL COLLABORATIVE LEARNING DALAM PENGEMBANGAN PENDIDIKAN SENI BUDAYA BERBASIS KEARIFAN LOKAL: SEBUAH KAJIAN LITERATURE REVIEW - Fadel Muhammad; Suci Fajrina; Rosta Minawati; Nursyirwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Cultural arts education in the 21st century requires innovation that can integrate traditional values with collaborative, creative, and communicative skills. The Barzanji tradition, as a form of Islamic religious music, has great potential to be developed in the context of education as a medium for preserving cultural and spiritual values. This article is a literature review that aims to examine the application of the Collaborative Learning model in Barzanji learning and its role in fostering awareness of the preservation of traditional Islamic music among students. The study was conducted through an analysis of various scientific sources, such as journals, proceedings, and research reports discussing the integration of Collaborative Learning in arts learning based on local wisdom. The results show that teaching Barzanji through the Collaborative Learning model can increase students' active participation, responsibility, and sense of togetherness, while strengthening religious, social, and aesthetic values. Thus, collaborative learning based on the Barzanji tradition has the potential to be an effective alternative strategy in the development of local wisdom-based cultural arts education in the 21st century